»When the Oldies Act like Children«: the Subversion of Aetonormativity in Skubic’s Youth Novel - Zorman, Barbara (Trideset let literarne nagrade večernica, 2026)
The analysis of the young adult novel Lahko bi umrl na tem kavču z mano (2024) by Andrej E. Skubic.draws on Gaja Kos’s theory of the Slovenian (young adult) problem novel and Maria Nikolajeva’s concept of aetonormativity. It argues that the novel retains several characteristics of the problem novel, such as its systematic portrayal of the crises the adolescent characters confront. However, it departs from the established model through its use of third-person narration, its focus on a group rather than an individual protagonist, and its more optimistic portrayal of characters and narrative development. The subversion of aetonormativity is achieved through resistance to heteronormativity, which is encouraged by the character’s experience in the digital sphere, through the deconstruction of adult authority, the carnivalization of the school environment, and the incorporation of adolescent discourses, media cultures, and communicative codes into the novel. The conclusion demonstrates that the novel reconfigures the relationship between young people and adults and opens new perspectives for reflecting on aetonormativity in the Slovenian young adult novel.